(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article discusses the analytical aspects of ensuring the assessment of the safety of production and sale of products in organizations. The focus is on the methodological tools used by specialists to diagnose and solve security problems. Practical examples of the implementation of analytical methods in production processes are given. Cases illustrating effective approaches to product safety are discussed. The conclusion is made about the importance of an integrated approach to safety assessment at all stages of the value chain.